Management of myelofibrosis during pregnancy: A case report - Živković, Radmila; Marković, Olivera; Marisavljević, Dragomir; Terzić, Tatjana; Tukić, Ljiljana (Vojnosanitetski pregled, 2015)
Introduction. Primary myelofibrosis (PMF) is a clonal myeloproliferative neoplasm that occurs most commonly in the decade six of life and it is very rare in the young persons. Case report. We reported a 28-year-old female patient with primary myelofibrosis who had a normal pregnancy and delivery in the week 40 of pregnancy without any complications. Two years before the diagnosis of PMF she had normal pregnancy. The patient was treated with interferon-alpha and low dose aspirin during the whole pregnancy and with low-molecular-weight heparin a week before delivery and 6 weeks after. The patient had no complications during pregnancy. She delivered in term with healthy, normal baby weight. Conclusion. Decision about treatment strategy of pregnancy associated hematologic malignancies should be made for each patient individually.
Keywords: myeloproliferative disorders; primary myelofibrosis; pregnancy; interferon-alpha; treatment outcome